Bilateral compressive neuropathy of the common peroneal nerve, secondary to multiple hereditary exostosis in an adolescent patient: a case report - Cáceres Ramón, Andrea Guadalupe; Alayón Vázquez, Victor Manuel; Espinosa Valencia, Javier Eduardo; Noguera Echeverría, Alexis Emir; Ibarra Guerrero, María Fernanda; Herrera Villaseñor, Enzo Alejandro; Quiroz Domínguez, Andrea Polett; Romero Díaz, Lisandro; Vargas Vázquez, Marco Esteban; Villalobos Cetina, Marco Alan; Madariaga Ramírez, Emiliano Francisco; Bello Olivera, Maritza Aime; et al. (International Journal of Research in Medical Sciences, 2025)
Osteochondroma is the most common bone tumor, accounting for 10-15% of all skeletal tumors and 20-50% of benign ones. These lesions can compress adjacent neurological structures, causing pain, paraesthesia, claudication, and progressive deficit. Common peroneal nerve (CPN) neuropathy is the third most frequent peripheral neuropathy in the lower extremity. Chronic nerve compression can lead to progressive symptoms and permanent neurological deficits if left untreated. Early diagnosis and proper follow-up are crucial. We present the case of a 16-year-old Mexican adolescent with compressive neuropathy of the common peroneal nerve secondary to multiple exostoses. The patient experienced tingling in both legs and dorsum of the feet, and progressive difficulty in dorsiflexion of the right foot. Physical examination revealed bilateral weakness in dorsiflexion, foot eversion, and hallux extension, as well as sensory alteration on the lateral aspect of both legs and dorsum of the feet. Electromyography confirmed decreased nerve conduction velocity in both common peroneal nerves. Surgical treatment with bilateral decompression of the common peroneal nerve and resection of the bony masses was decided. After three months of follow-up, the patient showed improvement in muscle strength and recovery of sensation. Timely surgical resection allows for functional recovery and avoids permanent sequelae. In patients with bilateral symptoms, early evaluation and treatment are critical to preserve motor function and improve quality of life.